The role of predictability in the stress response of a cichlid fish - Galhardo, Leonor (2012)
In recent years there has been an increasing interest in the cognitive abilities of fish with implications for animal welfare and management of rearing operations. Although it is known that psychological factors can modulate the stress response in mammals, this aspect has seldom been investigated within stress in fish. In this study we investigate whether the perception (appraisal) that fish make of significant environmental events modifies their behavioural and physiological response. For this purpose we have used a predictable vs. unpredictable paradigm for positive (feeding) and negative (confinement) events using the cichlid fish Oreochromis mossambicus as a model species. Results show that there is a differential effect of predictability for the feeding and confinement events. In the confinement experiment, predictability involved more attention to the visual cue and lower cortisol. The feeding event triggered higher levels of anticipatory behaviour and a tendency for higher cortisol in the predictable group. Therefore, predictable negative events reduce the cortisol response. Predictable positive events may elicit an anticipatory response, and when there is a significant delay between the visual cue and the actual occurrence of the event, it may also contain elements that can be interpreted as a stress response. These findings demonstrate that fish can appraise relevant aspects of the environment, with welfare implications for housing, husbandry and experimental procedures.